Differential Effects of Omeprazole and Lansoprazole Enantiomers on Aryl Hydrocarbon Receptor in Human Hepatocytes and Cell Lines - Novotna, Aneta; Srovnalova, Alzbeta; Svecarova, Michaela; Korhonova, Martina; Bartonkova, Iveta; Dvorak, Zdenek (PLOS ONE, 2014)
Proton pump inhibitors omeprazole and lansoprazole contain chiral sulfur atom and they are administered as a racemate, i.e. equimolar mixture of S- and R-enantiomers. The enantiopure drugs esomeprazole and dexlansoprazole have been developed and introduced to clinical practice due to their improved clinical and therapeutic properties. Since omeprazole and lansoprazole are activators of aryl hydrocarbon receptor (AhR) and inducers of CYP1A genes, we examined their enantiospecific effects on AhR-CYP1A pathway in human cancer cells and primary human hepatocytes. We performed gene reporter assays for transcriptional activity of AhR, RT-PCR analyses for CYP1A1/2 mRNAs, western blots for CYP1A1/2 proteins and EROD assay for CYP1A1/2 catalytic activity. Lansoprazole and omeprazole enantiomers displayed differential effects on AhR-CYP1A1/2 pathway. In general, S-enantiomers were stronger activators of AhR and inducers of CYP1A genes as compared to R-enantiomers in lower concentrations, i.e. 1–10 µM for lansoprazole and 10–100 µM for omeprazole. In contrast, R-enantiomers were stronger AhR activators and CYP1A inducers than S-enantiomers in higher concentrations, i.e. 100 µM for lansoprazole and 250 µM for omeprazole. In conclusion, we provide the first evidence of enantiospecific effects of omeprazole and lansoprazole on AhR signaling pathway.